2016
DOI: 10.1080/00016489.2016.1262552
|View full text |Cite
|
Sign up to set email alerts
|

Inter-observer agreement of paranasal sinus computed tomography scans

Abstract: In general, there was moderate inter-observer agreement of the structures by Cohen's kappa coefficient. Poor reproducibility was observed in the following structures: optic nerve, insertion of the uncinated process, anterior ethmoidal artery, and Keros class.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…Therefore, the presented ICC results are much more informative on the extent of interrater agreement. As expected, the kappa values for the LM scores of the current study fit well into existing literature (data not shown) (7,10,11) .…”
Section: Interrater Agreement and Degree Of Opacification And Diagnosissupporting
confidence: 90%
“…Therefore, the presented ICC results are much more informative on the extent of interrater agreement. As expected, the kappa values for the LM scores of the current study fit well into existing literature (data not shown) (7,10,11) .…”
Section: Interrater Agreement and Degree Of Opacification And Diagnosissupporting
confidence: 90%
“…All CRSsNP patients underwent sinus CT at the Tampere University Hospital as previously described. 11 All control subjects and 14 CRSsNP patients underwent MRI at the Terveystalo Healthcare Oyj, Tampere. MRI was performed during the same day when CT scans were performed in the CRSsNP group.…”
Section: Methodsmentioning
confidence: 99%
“…He filled a form of LM scores and other sinonasal structures as previously described. 11 For this study, we used LM scores and signs of sinus mucosal abnormality. Sinus mucosal abnormality was scored: 0 ¼ normal mucosa or sinus cyst, 1 ¼ mild mucosal swelling/thickened mucosa without signs of discharge, and 2 ¼ polypous mucosa AE signs of discharge.…”
Section: Sinus Imagingmentioning
confidence: 99%
“…meeting with inclusion/exclusion criteria), from a random sample of 69 CRSwNP patients who had undergone nasal polyp biopsy during ESS consultation/ESS at Tampere University Hospital between 2005–2007; (ii) thirty-eight CRSwNP patients eligible from a random sample of 246 CRS patients who had undergone ESS consultation between 2002–2017 at the Helsinki and Tampere University Hospitals; (iii) six CRSwNP patients eligible form a random sample of 97 CRS/rhinitis patients who underwent sinus CT scans due to suspicion of CRS at Tampere University Hospital during 2006–2011. 32 …”
Section: Subjectsmentioning
confidence: 99%